2017
DOI: 10.1002/chem.201702561
|View full text |Cite
|
Sign up to set email alerts
|

The Design of a New Cobalt Sulfide Nanoparticle Implanted Porous Organic Polymer Nanohybrid as a Smart and Durable Water‐Splitting Photoelectrocatalyst

Abstract: Development of an inexpensive, efficient and robust nanohybrid catalyst as a substitute for platinum in photoelectrocatalytic hydrogen production has been considered intriguing and challenging. In this study, the design and sequential synthesis of a novel cobalt sulfide nanoparticle grafted Porous Organic Polymer nanohybrid (CoS @POP) is reported and used as an active and durable water-splitting photoelectrocatalyst in the hydrogen evolution reaction (HER). The specific textural and relevant chemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…On Pd@Al 2 O 3 , we achieved 75% AP conversion and 3% selectivity to EB after 60 min reaction time and TOF was 3.80 min -1 . The higher TOF of Pd@Ph-POP could be assigned to the higher oxygen content, which helps in homogeneous dispersion of Pd nanoparticles and presence of electron-rich Pd formed through the strong electronic interaction between Pd and O atoms in the polymer framework which had been confirmed from comparison of XPS analysis of bare Ph-POP and Pd@Ph-POP (Figure S13, SI), 14 facilitating hydrogenation over the electron-enriched metallic Pd. 13 The superior selectivity towards EB of Pd@Ph-POP (100%) than Pd@Al 2 O 3 (3%) under similar reaction conditions could correspond to the strong effect of the hydroxyl rich polymer support acidity promoting dehydration route of PhE to EB transformation, as evidenced from higher surface acid strength of Ph-POP (1.603 mmol/g) compared to alumina (0.936 mmol/g) determined from NH 3 -TPD measurement which is in good agreement with the work reported by Chen et al 12 lectivity was observed at above 60 o C which could be assigned to appearance of ethylcyclohexane (EC) as side product triggered by the over hydrogenation of the benzene ring (Figure S14).…”
Section: Catalytic Investigationmentioning
confidence: 81%
“…On Pd@Al 2 O 3 , we achieved 75% AP conversion and 3% selectivity to EB after 60 min reaction time and TOF was 3.80 min -1 . The higher TOF of Pd@Ph-POP could be assigned to the higher oxygen content, which helps in homogeneous dispersion of Pd nanoparticles and presence of electron-rich Pd formed through the strong electronic interaction between Pd and O atoms in the polymer framework which had been confirmed from comparison of XPS analysis of bare Ph-POP and Pd@Ph-POP (Figure S13, SI), 14 facilitating hydrogenation over the electron-enriched metallic Pd. 13 The superior selectivity towards EB of Pd@Ph-POP (100%) than Pd@Al 2 O 3 (3%) under similar reaction conditions could correspond to the strong effect of the hydroxyl rich polymer support acidity promoting dehydration route of PhE to EB transformation, as evidenced from higher surface acid strength of Ph-POP (1.603 mmol/g) compared to alumina (0.936 mmol/g) determined from NH 3 -TPD measurement which is in good agreement with the work reported by Chen et al 12 lectivity was observed at above 60 o C which could be assigned to appearance of ethylcyclohexane (EC) as side product triggered by the over hydrogenation of the benzene ring (Figure S14).…”
Section: Catalytic Investigationmentioning
confidence: 81%
“…The O 1s XPS spectra (Figure 4 B) are consisted as having three kinds of oxygen species. Peak O α located at 529.0 eV corresponds to lattice oxygen species; peak O β at 531.3 eV is contributed by the presence of absorbed oxygen species; peak O γ at 532.5 eV is assigned to the absorbed H 2 O [32] . The apparently largest amount of absorbed oxygen species on LCB‐7 suggests it has the most O v .…”
Section: Resultsmentioning
confidence: 99%
“…CoS x @POP has been evaluated as a superior photoelectrocatalyst in HER, achieving a current density of 6.43 mA cm −2 at 0 V versus the reversible hydrogen electrode (RHE) in a 0.5 m Na 2 SO 4 electrolyte which outperforms its Co 3 O 4 @POP analogue. (Scheme ) . The BET surface areas of Co 3 O 4 @POP and CoS x @POP were found to be 582 and 489 m 2 g −1 respectively.…”
Section: Synthesis Of Pop Through Oxidative Polymerization and Its Pomentioning
confidence: 99%